Metastasis of cervical cancer to breast: A case report and review of literature - Ankit Mangla; Nikki Agarwal; Farid Saei Hamedani; Jiaxiang Liu; Shweta Gupta; Michael R. Mullane (Elsevier, 2017)
Metastasis to the breast from an extra-mammary malignancy has been documented in literature, however cervical cancer metastasis to the breast is very rare. Thirty-eight cases of metastatic deposit to the breast from cervical cancer have been reported in literature. Though most patients present with a breast lump, it is very difficult to clinically distinguish a primary breast malignancy from a metastatic deposit. Histopathology of the tissue, aided with immune-histochemical staining pattern provides a definitive diagnosis. Our patient, a 51-year old woman presented with breast lump and history of post-menopausal bleeding. Upon further workup, the patient was diagnosed with cervical cancer. The mammogram and ultrasound of the breast showed multiple lumps within the breast. Histopathology of the breast mass showed metastatic deposit in the breast from cervical cancer. The patient was treated with radiation therapy to the cervix along with concurrent chemotherapy for local control of pain. After completion of local treatment, she started systemic chemotherapy, however she developed health-care associated pneumonia and subdural hematoma leading to deterioration in her performance status. The patient opted for hospice care and died 2 months later. In this report, we will review the presentation of the 38 cases reported in literature and the imaging and histopathologic findings of metastatic deposits to the breast.